2017
DOI: 10.1210/jc.2017-01471
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Parathyroid Hormone Effect on Health-Related Quality of Life in Adults With Chronic Hypoparathyroidism

Abstract: Treatment with rhPTH(1-84) may improve HRQoL in adults with hypoparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 19 publications
3
61
1
2
Order By: Relevance
“…Well-being was not being assessed in this study, but previous data showed failure to restore well-being in patients with HP with standard therapy of calcium and vitamin D (18,19). Therapy with rhPTH 1-84 may help to improve the quality of life in these patients (20). Hospitalization due to hypocalcaemia was rather rare in this study, having occurred in 5% of the cohort, with 75% of the hospitalizations occurring at the time of HP diagnosis and not during follow-up.…”
Section: Discussionmentioning
confidence: 85%
“…Well-being was not being assessed in this study, but previous data showed failure to restore well-being in patients with HP with standard therapy of calcium and vitamin D (18,19). Therapy with rhPTH 1-84 may help to improve the quality of life in these patients (20). Hospitalization due to hypocalcaemia was rather rare in this study, having occurred in 5% of the cohort, with 75% of the hospitalizations occurring at the time of HP diagnosis and not during follow-up.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, hypoparathyroid patients often describe neurocognitive complaints, including anxiety, depression, fatigue, and various cognitive deficits 13 , 18 , 34 , 35 . They have lower QoL scores, using validated tools, mostly the Short Form Health Survey 36 (SF-36), a self-administered 36-item questionnaire, compared with reference norms 18 , 19 , 34 , 36 , 37 . Both mental and physical domains are affected, although the mechanisms for the deficits are uncertain.…”
Section: Quality Of Life Complicationsmentioning
confidence: 99%
“…Anecdotally, patients report marked improvements, but a significant favorable effect of PTH-replacement therapy was not shown in double-blind randomized trials compared with controls receiving conventional therapy 20 , 36 . In the REPLACE study, SF-36 scores did not differ between the two treatment arms, rhPTH(1-84) versus placebo, at 24 weeks 36 . One can speculate that this negative finding was due to the lack of sustained PTH elevations with the frequency of PTH administration used.…”
Section: Quality Of Life Complicationsmentioning
confidence: 99%
“…From these 31 studies, four studies were finally included in this meta-analysis based on the selection criteria as mentioned above. Rest of the studies were excluded because of the following reasons: study done in children;[ 10 ] prospective design or unrelated population[ 11 12 13 25 26 27 28 29 30 31 32 33 34 35 36 ]; duplication of data[ 37 38 ]; comparison of different PTH doses[ 39 40 41 ]; evaluation of cost-effectiveness of PTH therapy[ 42 ]; and use of either pump therapy or continuous subcutaneous PTH infusion. [ 5 43 44 45 46 ]…”
Section: R Esultsmentioning
confidence: 99%